Basic Principles and Methods of Using Media Education for Forming Students’ Analytical Thinking - Mambetkarimov Rinat (Zien Journals, 2021)
This article deals with the basic principles and techniques of media education to form analytical thinking of students It also examines film analysis, creative and imitation media education exercises. The development of students’ skills to communicate and discuss, to prove their point of view with reason is always a relevant task in the educational landscape of modern higher school. One of the optimal ways to develop analytical interdisciplinary competence is media education, which allows the students to carry out the process of analysis and synthesis of information on the example of works of media culture of various types and genres. The authors consider the possibilities of using media educational methods and technologies in the process of civil and patriotic education, give examples of creative tasks of various types (literary-imitation, theatrical-situational, visual-imitation, etc.) for the formation of analytical thinking of the younger generation. In this way the student body gets an opportunity to evaluate works of media culture independently, develop their creative potential, learn to perceive media projects thoroughly, get new knowledge, develop communicative competences. The data provided by the authors of the paper can confirm the need of use of the educational, educational and developing media education potential for the Russian educational organizations, relevance of the questions connected with strengthening of interaction of various educational structures and scientific education centers in the field of media pedagogy for further development of methodical tools in the solution of the problems of development of media competence of the younger generation.
Keywords: Media; Media Education; Media Competency; Students